Genome-level identification of cell wall invertase genes in wheat for the study of drought tolerance - Webster, H.; Keeble, G.; Dell, B.; Fosu-Nyarko, J.; Mukai, Y.; Moolhuijzen, Paula; Bellgard, M.; Jia, J.; Kong, X.; Feuillet, C.; Choulet, F.; Appels, R. (2012)
In wheat (Triticum aestivum L.) drought-induced pollen sterility is a major contributor to grain yield loss and is caused by the downregulation of the cell wall invertase gene IVR1. The IVR1 gene catalyses the irreversible hydrolysis of sucrose to glucose and fructose, the essential energy substrates which support pollen development. Downregulation of IVR1 in response to drought is isoform specific and shows variation in temporal and tissue-specific expression. IVR1 is now prompting interest as a candidate gene for molecular marker development to screen wheat germplasm for improved drought tolerance. The aim of this study was to define the family of IVR1 genes to enable: (1) individual isoforms to be assayed in gene expression studies; and (2) greater accuracy in IVR1 mapping to the wheat genetic map and drought tolerance QTL analysis. Using a cell wall invertase-specific motif as a probe, wheat genomics platforms were screened for the presence of unidentified IVR1 isoforms. Wheat genomics platforms screened included the IWGSC wheat survey sequence, the wheat D genome donor sequence from Aegilops tauschii Coss, and the CCG wheat chromosome 3B assembly: contig506.Chromosome-specific sequences homologous to the query motif were isolated and characterised. Sequence annotation results showed five previously unidentified IVR1 isoforms exist on multiple chromosome arms and on all three genomes (A, B and D): IVR13A, IVR14A, IVR15B, IVR1.23B and IVR1-5D. Including three previously characterised IVR1 isoforms (IVR1.11A, IVR1.21A and IVR1.13B), the total number of isoform gene family members is eight. The IVR1 isoforms contain two motifs common to cell wall invertase (NDPN and WECPDF) and a high degree of conservation in exon 4, suggesting conservation of functionality. Sequence divergence at a primary structure level in other regions of the gene was evident amongst the isoforms, which likely contributes to variation in gene regulation and expression in response to water deficit within this subfamily of IVR1 isoforms in wheat.